The incidence and outcomes of out-of-hospital cardiac arrest in metropolitan versus rural locations: A systematic review and meta-analysis. (April 2023) - Smith, Ashlea; Masters, Stacey; Ball, Stephen; Finn, Judith
Abstract: Background/aims: Rurality poses a unique challenge to the management of out-of-hospital cardiac arrest (OHCA) when compared to metropolitan (metro) locations. We conducted a systematic review of published literature to understand how OHCA incidence, management and survival outcomes vary between metro and rural areas. Methods: We included studies comparing the incidence or survival of ambulance attended OHCA in metropolitan and rural areas, from a search of five databases from inception until 9th March 2022. The primary outcomes of interest were cumulative incidence and survival (return of spontaneous circulation, survival to hospital discharge (or survival to 30 days)). Meta-analyses of OHCA survival were undertaken. Results: We identified 28 studies (30 papers- total of 823, 253 patients) across 13 countries of origin. The definition of rurality varied markedly. There was no clear difference in OHCA incidence between metro and rural locations. Whilst there was considerable statistical heterogeneity between studies, the likelihood of return of spontaneous circulation on arrival at hospital was lower in rural than metro locations (OR = 0.53, 95% CI 0.40, 0.70; I 2  = 89%; 5 studies; 90, 934 participants), as was survival to hospital discharge/survival to 30 days (OR = 0.52, 95% CI 0.38, 0.71; I 2  = 95%; 15 studies; 18, 837 participants). Conclusions: Overall, while incidence did not vary, the odds of OHCA survival to hospital discharge were approximately 50% lower in rural areas compared to metro areas. This suggests an opportunity for improvement in the prehospital management of OHCA within rural locations. This review also highlighted major challenges in standardising the definition of rurality in the context of cardiac arrest research.